Rumores y fantasías sociales La tragedia de Alianza Lima, 1987 - Panfichi, Aldo (2006)
This article explores the fantasies and legends that emerged when a plane carrying the young football team of Alianza Lima crashed into the Pacific Ocean a few minutes before landing in the capital city of Lima, Peru on December 8, 1987. It focuses on the martyrs of this crash and, more specifically, the stories and versions of history that emerged in its wake. As the narrative reveals, these interpretations laid blame for the disaster on corrupt politicians, drug traffickers, and the Peruvian Navy. The article locates this tragedy in the dramatic social and political context of Peru in the 1980s, which was marked by economic crisis, corruption, political violence and despair. Finally, we argue that the responses that this incident provoked among soccer fans offered them an opportunity to express the much deeper cultural and political differences present in contemporary Peru.